Making Development Political: NGOs as Agents for Alternatives to Development - Schöneberg, Julia (Nomos Verlagsgesellschaft mbH & Co. KG, 2016)
“Development has failed”. Departing from this Post-Development claim, the book reveals how existent and perceived rules and restrictions of the global development system work in maintaining inequalities between international non-governmental organisations (INGOs) and Haitian organisations. To counter these structures, the author proposes a form of “development-as-politics”, in which local and international actors engage in selective, political interaction. Findings provide the starting point for practical alternatives that account for the voices of the subaltern and enable international NGOs to assume a role that supports rather than weakens local capacities.Julia Schöneberg’s analysis is based on her field research in Haiti between 2012 and 2014. Her research interests include alternative approaches to development and Post-Development, social movements, racism and post-colonialism.